Flap Monitoring Using Transcutaneous Oxygen or Carbon Dioxide Measurements - Halani, Sameer H.; Hembd, Austin S.; Li, Xingchen; Kirby, Ben; Beard, Courtney C.; Haddock, Nicholas T.; Suszynski, Thomas M. (Journal of Hand and Microsurgery, 2020)
Free tissue transfer is a cornerstone of complex reconstruction. In many cases, it represents the last option available for a patient and their reconstruction. At high-volume centers, the risk of free flap failure is low but its occurrence can be devastating. Currently, the mainstay for flap monitoring is the clinical examination. Though reliable when performed by experienced clinicians, the flap exam is largely subjective, is performed discontinuously, and often results in significant time delay between detection of flap compromise and intervention. Among emerging flap monitoring technologies, the most promising appear to be those that rely on noninvasive transcutaneous oxygen and carbon dioxide measurements, which provide information regarding flap perfusion. In this article, we review and summarize the literature on various techniques but primarily emphasizing those technologies that rely on transcutaneous gas measurements. We also define characteristics for the ideal flap monitoring tool and discuss critical barriers, predominantly cost, preventing more widespread utilization of adjunct monitoring technologies, and their implications.
Keywords: flap monitoring; transcutaneous oxygen; carbon dioxide; systematic review